Global solutions and their limit behavior for parabolic inclusions with an unbounded right-hand part - Kapustyan, O.; Bezushchak, D.; Stanzhytskyi, O.; Korol, I. (Carpathian Mathematical Publications, 2024)
We study global resolvability for parabolic inclusions with an upper semicontinuous multi-valued right-hand part of more than linear growth. Theorems about the existence of global mild solutions in different phase spaces are proved. Limit sets for the obtained global solutions in the corresponding phase spaces are investigated.